Impact of a single treatment of injectable doramectin on weight gain post weaning in beef heifers and steers in central Queensland, Australia. Issue 6 (28th May 2019) - Taylor, LF; Hodge, A
Abstract : Objectives: To demonstrate the impact of a single drench with a label dose of injectable doramectin subsequent to weaning on the growth and performance of heifers and steers in central Queensland beef herds. Methods: Three studies were undertaken on recently‐weaned Bos indicus‐ cross beef calves with ≥ 75% B. indicus content on two farms in central Queensland, just north of the Tropic of Capricorn. Farm 1 was located 50 km north and Farm 2 75 km north‐west of Rockhampton. In each study, half of a group of recently‐weaned beef calves were treated by random allocation with 0.2 mg/kg of injectable doramectin, and the remainder acting as untreated controls. Study 1 (Farm 1) enrolled 250 heifers, while studies 2 and 3 (Farm 2) both enrolled 200 steers and 200 heifers. The farms involved did not historically use macrocyclic lactone‐based drenches on their cattle. There were varying periods of follow‐up, with treated and control cattle pastured as one group throughout the study period. Worm burdens were monitored using standard faecal egg counts and larval differentiation procedures. In all studies, the worm genera present were a mix of Cooperia spp., Haemonchus spp. and Oesophagostomum spp. Results: In study 1, conducted on Farm 1 beginning 9 July 2012, doramectin‐treated cattle gained an average of 0.27 kg/day while control cattle gained 0.19 kg/day over a monitoring period of 121 days (P < 0.0001). In study 2, conducted on Farm 2 beginning 28 July 2015, doramectin‐treated cattle gained an average of 0.15 kg/day versus 0.145 kg/day in the control group (P = 0.44) over a 231‐day study period. In study 3, conducted on Farm 2 beginning 4 August 2016, doramectin‐treated steers and heifers gained an average of 0.431 and 0.402 kg/day versus 0.342 and 0.311 kg/day in the control group, respectively, over the first 91 days of the study (P < 0.0001 in both cases). The differences in average daily gain (ADG) in subsequent time periods were not statistically significant for steers or heifers. However, overall differences in ADG from day 0 remained statistically significant out to day 258, when the study ended for the heifers. By day 594, when the study ended for the steers, the difference in ADG was no longer significant. Conclusion: Treatment with injectable doramectin soon after weaning resulted in improved weight gain in the 3 months after weaning in two of the three studies.